Dual-Role Ubiquitination Regulation Shuttling the Entire Life Cycle of the Flaviviridae - Cai, Dongjie; Liu, Lingli; Tian, Bin; Fu, Xingxin; Yang, Qiyuan; Chen, Jie; Zhang, Yilin; Fang, Jing; Shen, Liuhong; Wang, Ya; Gou, Liping; Zuo, Zhicai (Frontiers in Microbiology, 2022)
Ubiquitination is a reversible protein post-translational modification that regulates various pivotal physiological and pathological processes in all eukaryotes. Recently, the antiviral immune response is enhanced by the regulation of ubiquitination. Intriguingly, Flaviviridae viruses can ingeniously hijack the ubiquitination system to help them survive, which has become a hot topic among worldwide researchers. The Flaviviridae family members, such as HCV and CSFV, can cause serious diseases of humans and animals around the world. The multiple roles of ubiquitination involved in the life cycle of Flaviviridae family would open new sight for future development of antiviral tactic. Here, we discuss recent advances with regard to functional roles of ubiquitination and some ubiquitin-like modifications in the life cycle of Flaviviridae infection, shedding new light on the antiviral mechanism research and therapeutic drug development.